South Africa - Results-Based Financing and the Book Supply Chain : Motivating Writers and Publishers to Create Quality Storybooks - World Bank Group (World Bank, Washington, DC, 2020)
Literacy serves as an essential building block for learning, so when children master reading, they are more likely to succeed in school generally. To support the South African government’s campaign to improve literacy rates and foster a love of reading among children, room to read implemented an initiative that included results-based elements to increase the availability of affordable, quality storybooks in African languages. The project brought together public and private sector players in the book supply chain to develop new national standards on storybooks and translations, and helped to identify and build capacity of smaller publishers and writers to publish African-language storybooks. In doing so, the project demonstrated how results-based financing can be effective in the production and procurement stages of the book chain in South Africa. Results-based financing motivated and engaged publishers and writers to participate and stay engaged in the two-year project, which armed them with the skills and knowledge they need to continue to create and publish quality storybooks on their own. The success of the South Africa project underscores the potential of using innovative models such as pooled procurement, open licensing, and one day one book workshops along with results-based financing to increase the availability of quality children’s books in a cost-efficient manner. By strengthening the book chain, the project ultimately helped to foster children’s love of reading and helped them to become better learners.